E-Marketing as a Business Advantage for Improving Sme’s Competitiveness in Lombok Island -Indonesia - Renny; Nurcahyo, Bagus; Setyawati, Dyah Mieta; Sutanty, Ety (Archives of Business Research, 2016)
The success of Small and Medium Enterprises (SMEs) is the availability of a clear market for the products. Meanwhile, the fundamental weaknesses faced by SMEs in marketing are low market orientation, weakness in a complex and sharp competition and inadequate marketing infrastructure. Faced with an increasingly open market mechanisms and competitive, market control is prerequisite for improving competitiveness. Therefore, expansion of market access with Web-based Information Technology is now needed as a medium for global communication. One thing that gives a competitive advantage in international trade competition is information technology of electronic marketing or e-marketing. This paper intend to shows the important role of e-marketing for SMEs in Lombok Island - Indonesia and how to develop the model of e-marketing.